The Use of the Ghetto Metaphor in the Memory Culture of the Sephardic Community in Belgrade between the Two World Wars (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2025)
This paper examines the presence of the ghetto metaphor in the discourse of remembrance of the Sephardim in Belgrade regarding the past of their community. The corpus consists of texts from Jewish publications from the interwar period, in which the historical term «ghetto» is metaphorically projected onto the Jewish quarter of Belgrade (Jalija). The research is based on the theoretical and methodological framework of critical sociolinguistics and (historical) discourse analysis, and also includes terminology and some postulates from memory studies and metaphor studies in cognitive linguistics. This approach aims to examine the role and meaning of the ghetto metaphor in narrative discourse and relate it to the dominant ideologies of the Sephardic community in Belgrade.The qualitative analysis of the corpus shows that this metaphor takes the form Jalija is a ghetto and that, in the examined utterances, it serves to designate the traditional Jewish quarter as a physical and spiritual obstacle to the modernization of the community. The frequent and uncritical representation of the Jewish quarter reflects an orientalist discourse through which the authors expressed negative attitudes toward the patriarchal past of the community and beliefs in the superiority of modern society over traditional. However, although the use of this metaphor predominates in the corpus, in certain utterances the metaphorical projection is absent. In these cases, the Sephardic quarter of Belgrade is compared to the ghetto only in spatial terms, and while the authors distance themselves from it by characterizing it as “primitive” and “backward,” they nonetheless assign a positive value to its symbolic nature.
Keywords: interwar Jewish (Sephardic) authors; Jewish quarter of Belgrade (Jalija); ghetto; metaphor in memory discourse; ideologies of modernization